KONTRIBUSI MOTIVASI BERPRESTASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA DOSEN FKIP UPP - -, Hardianto (Edu Research, 2015)
The purposes of the research were to find out the contribution of achievement motivation and style management toward individual and colective lecturers’ job working. The main purpose of the research was to increase the lecturers’ job working at Education Faculty of Pasir Pengaraian University. Then the output of this research was expected to get in Licensed National Journal or Research Prosiding. The research was done by the quantitative Expost Facto formed. The population of the research was 36 lecturers and sample was chosen by using total sampling technique.The intruments used Linkert Scale with 5 alternative answers. The research spent time about 1 year.